2018
DOI: 10.1016/j.neuro.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Moderate perinatal thyroid hormone insufficiency alters visual system function in adult rats

Abstract: Thyroid hormone (TH) is critical for many aspects of neurodevelopment and can be disrupted by a variety of environmental contaminants. Sensory systems, including audition and vision are vulnerable to TH insufficiencies, but little data are available on visual system development at less than severe levels of TH deprivation. The goal of the current experiments was to explore dose-response relations between graded levels of TH insufficiency during development and the visual function of adult offspring. Pregnant L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The observations in humans are supported by rodent studies where neurodevelopmental impairments result from moderate and transient reductions in serum TH induced by chemical exposures (Ausó et al. 2004; Boyes et al. 2018; Gilbert 2011; Gilbert et al.…”
Section: Discussionmentioning
confidence: 74%
“…The observations in humans are supported by rodent studies where neurodevelopmental impairments result from moderate and transient reductions in serum TH induced by chemical exposures (Ausó et al. 2004; Boyes et al. 2018; Gilbert 2011; Gilbert et al.…”
Section: Discussionmentioning
confidence: 74%
“…This may suggest a role for thyroid hormone in visual processing in the inner retina but this remains to be explored. It has been reported that hypothyroidism impairs visual-evoked potentials in central pathways in rats ( 13 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone also influences photoreceptor differentiation and survival. Hypothyroidism in rodents impairs M opsin expression ( 10 12 ) and responses to green wavelength light ( 13 ). Hyperthyroidism can alter opsin expression ( 14 ) but excesses cause cone cell death in mice ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Population studies have revealed that high serum thyrotropin levels are associated with retinal arteriolar narrowing [8]. Animal studies have demonstrated that moderate levels of pre- and postnatal TH insufficiency lead to alterations in visual function in adult rats [9]. These findings highlight the important role of TH in regulating various visual functions.…”
Section: Introductionmentioning
confidence: 99%